Édition et nicodémisme dans l’Italie du xvie siècle - Dominique Fratani (Les Cahiers de Framespa)
This analysis focuses on what is a relatively little known aspect of works published in 16th century Italy, and concerns the relations between the ecclesiastical sphere, aspiring to a renovatio ecclesiae, and that of the publishing industry, particularly between 1542 and 1560. Following the Reformation, the Catholic church exercised severe repression against suspected heretics in the Italian peninsular. The Waldensians, the « Spirituels », plus Evangelists and Catholic Reformers could make their views known through the emergence of epistolary compilations. This new genre rapidly took root, as it allowed the publication of ideas close to those of openly heterodox movements. The publishing phenomenon involved not only some of the most outstanding publishers and intellectuals of the time, but also some of the great figures of organized religion. The movement continued, sometimes in Nicodemite fashion, right up to 1559, when the Index Librorum Prohibitorum was published.